SOME ASPECTS ON THE ECOLOGY OF MANGROVE WHELK TELESCOPIUM TSLESCOPIUM (LINNE, 1758) (MOLLUSeA, GASTROPODA: POTAMIDIDAE) - ARIE BUDIMAN (Treubia, 1988)
An ecological sfudy of Telescopium telescopium was conducted in regard to its distribution and=density, and brief observations were made on its foraging activities, The study was carried out in 12 mangrove forests. distributed in Java, Maluku and Iric-i Jaya. The result indicates that the snail occured at a very low frequency and density. It may be due to its preference to an open area, 'as well as its restricted distribution within the forest, The shell is of two forms, the typical and the smooth form, There is a distinct habitat segregation between the two forms owing to the degree of shadiness, The time of activity is related to the tidal regime, with movement begun when animals are exposed to the air, During their inactive phase, these snails are burried into the muddy substrate. The fact that the animal are not active simultaneously leads into a suggestion that the snail is able to maintain its feeding activity from its burrow, even during high tide.